Enhancement of heterotrophic activities in polluted water by Bacillus coagulans BW-25 - Karim, Md Abdul; Happy, Rehena Nasrin; Masum, Mehedi Al; Hoque, Sirajul (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17867 J. Asiat. Soc. Bangladesh, Sci. 39(2): 269-272, December 2013